Movement and Stillness in one of Khaghani and Nezami’s Ode (Qasida) - Habibullah Kashefi (Randwick International of Education and Linguistics Science Journal, 2023)
Studying the works of the great figures of Persian literature creates hundreds of movements in the reader and there is no doubt that Khaghani and Nezami are among the brightest stars of this field. In this article, movement and stillness point of view of a poem by both poets has been firmly studied. Finally, after considering accurate statistical results, it has been shown that how much movement and stillness can be found in odes of these outstanding poets. It also has been shown that in the poems of which one of them, inanimate nature has more to do with parts of human life. In addition, an attempt has been made to accurately identify the positive and negative aspects of their static and dynamic poetry. Personification, Paradox, Simile, Metaphor, Color Element and other similar elements lead to dynamics of the images. The poets we are discussing have used them more and better according to their time. In addition, both poets have used less of the elements that lead to stagnation. Khaghani has taken pictures directly from nature and has shown his life experiences and Nezami has composed his ode imitating Khaghani's ode and borrowed some of his pictures. This subject has been studied and analyzed for the first time and in addition to comparing and measuring Khaghani and Nezami's odes from a dynamic and static point of view, their content has been considered in terms of common points. In order to do that, the elements involved in image dynamics are described in detail and then compared and reviewed.